Dendritic poly(silylene arylacetylene) resins based on 1, 3, 5-triethynylbenzene. (15th April 2020) - Luo, Jiawei; Liu, Xiaotian; Ma, Manping; Tang, Junkun; Huang, Farong
Graphical abstract: Highlights: The viscosities of dendritic DPSA resins at 90 °C are below 200 mPa·s and stable for 4 h. The flexural modulus of cured resins is up to 12.65 GPa. The Td5 and Yr800 of the cured resins in nitrogen are above 700 °C and 93%, respectively. Abstract: Dendritic poly(silylene arylacetylene) resins based on 1, 3, 5-triethynylbenzene were synthesized through Grignard reaction. The influences of the content of 1, 3, 5-triethynylbenzene on the properties of the resin including processability, mechanical properties, heat resistance and thermal stability are studied. Results show that dendritic poly(silylene arylacetylene) resins possess good processability and high mechanical properties while maintaining excellent heat-resistance and thermal stability. The viscosity of dendritic poly(silylene arylacetylene) resins at 90 °C are below 200 mPa·s, and the flexural modulus of the cured DPSA-43H resin is up to 12.65 GPa. The degradation temperatures at 5% weight loss and the residue yield at 800 °C of the cured resins in nitrogen are all above 700 °C and 93%, respectively.